1959
DOI: 10.1002/jlac.19596260115
|View full text |Cite
|
Sign up to set email alerts
|

Die Kondensation von Δ1‐Piperidein mit Acetessigsäure und Benzoylessigsäure zu Isopelletierin bzw. α‐Phenacyl‐piperidin

Abstract: Es wird die Synthese des Isopelietierins (X) und des m-Phenacyl-piperidins (XI) im pH-Bereich 6-12 beschrieben und gezeigt, unter welchen Bedingungen die Kondensation von Al-Piperidein rnit P-Ketosauren rnit guter Ausbeute durchfuhrbar ist. Einige theoretische Gesichtspunkte werden erlautert.Aldehydammoniake (I) kondensieren sich mit P-Ketosauren (11), wie wir erstmals zeigen konnten, rasch nach Gleichung (A) zu P-Aminoketonen (III), wenn man in wakiger Losung bei Zimmertemperatur in einem pH-Bereich zwischen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As shown in Scheme , we began our investigations by exploring whether cyclic nitrones of type 14 could provide an alternative to the well‐established decarboxylative Mannich‐type reaction between cyclic imines and β‐ketoacids (i.e. the Schöpf reaction) . Given that this imine variant is known to be slow, low‐yielding, and pH‐dependent with side reactions often observed, we anticipated that an alternative and broadly effective variant, even in racemic format, could be of value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme , we began our investigations by exploring whether cyclic nitrones of type 14 could provide an alternative to the well‐established decarboxylative Mannich‐type reaction between cyclic imines and β‐ketoacids (i.e. the Schöpf reaction) . Given that this imine variant is known to be slow, low‐yielding, and pH‐dependent with side reactions often observed, we anticipated that an alternative and broadly effective variant, even in racemic format, could be of value.…”
Section: Methodsmentioning
confidence: 99%
“…the Schöpf reaction) . Given that this imine variant is known to be slow, low‐yielding, and pH‐dependent with side reactions often observed, we anticipated that an alternative and broadly effective variant, even in racemic format, could be of value. Pleasingly, we found that 14 and 15 could readily merge, without any added catalyst, simply upon stirring in CH 2 Cl 2 at 23 °C.…”
Section: Methodsmentioning
confidence: 99%
“…25). Lysine was oxidized with N-bromosuccinirnide (26), and the product of this reaction, presumably As-piperideine, was condensed, n ithout isolation, with acetoacetic acid or benzoylacetic acid (14,19). The products, ( + )-pelletierine and ($)-a-phenacylpiperidine, respectively, were purified and isolated as hydrochlorides.…”
mentioning
confidence: 99%
“…As shown in Scheme 1, we began our investigations by exploring whether cyclic nitrones of type 14 could provide an alternative to the well-established decarboxylative Mannichtype reaction between cyclic imines and b-ketoacids (i.e.t he Schçpf reaction). [11] Given that this imine variant is known to be slow,l ow-yielding,a nd pH-dependent with side reactions often observed, [11,12] we anticipated that an alternative and broadly effective variant, even in racemic format, could be of value.P leasingly,w ef ound that 14 and 15 could readily merge,w ithout any added catalyst, [13] simply upon stirring in CH 2 Cl 2 at 23 8 8C. Table 1provides the products synthesized (19-27), where no further optimization was performed from our initial condition hit given the generally smooth and high yielding outcomes (50-90 %);t he one exception was product 26, obtained in 34 %yield from aconjugated starting material.…”
mentioning
confidence: 99%